2014
DOI: 10.1007/s10803-014-2049-2
|View full text |Cite
|
Sign up to set email alerts
|

A Parent-Mediated Intervention That Targets Responsive Parental Behaviors Increases Attachment Behaviors in Children with ASD: Results from a Randomized Clinical Trial

Abstract: The current study is a randomized clinical trial evaluating the efficacy of Focused Playtime Intervention (FPI) in a sample of 70 children with Autism Spectrum Disorder. This parent-mediated intervention has previously been shown to significantly increase responsive parental communication (Siller et al. in J Autism Dev Disord 43:540–555, 2013a). The current analyses focus on children’s attachment related outcomes. Results revealed that children who were randomly assigned to FPI showed bigger increases in attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 40 publications
1
55
0
Order By: Relevance
“…Koren-Karie and colleagues (2009) reported that the relationship between maternal sensitivity and attachment security in autism holds after controlling for children’s level of developmental functioning and responsiveness to mother during a separate interaction. In the study perhaps most clearly corroborating this sensitivity–security link, Siller, Swanson, Gerber, Hutman, and Sigman (2014) reported that an intervention aimed at improving caregiver sensitivity with children with autism led (post-intervention) to an increase in attachment behaviors exhibited by the children during a modified separation and reunion procedure.…”
Section: Maternal Behavior and Child Abilities As Correlates Of Attacmentioning
confidence: 77%
“…Koren-Karie and colleagues (2009) reported that the relationship between maternal sensitivity and attachment security in autism holds after controlling for children’s level of developmental functioning and responsiveness to mother during a separate interaction. In the study perhaps most clearly corroborating this sensitivity–security link, Siller, Swanson, Gerber, Hutman, and Sigman (2014) reported that an intervention aimed at improving caregiver sensitivity with children with autism led (post-intervention) to an increase in attachment behaviors exhibited by the children during a modified separation and reunion procedure.…”
Section: Maternal Behavior and Child Abilities As Correlates Of Attacmentioning
confidence: 77%
“…Subsequent portions of the intervention may then include increasing the child's interest in their play-partner than the RI (Mahoney & MacDonald, 2007). This type of intervention has demonstrated positive parent and child outcomes, including in the context of Responsive Teaching (Karaaslan, Diken, & Mahoney, 2013; Mahoney & MacDonald, 2007; Mahoney & Perales, 2005), Adapted Responsive Teaching (Baranek et al, 2015); Focused Playtime Intervention (Kasari, 2014; Siller, Hutman, & Sigman, 2013; Siller, Swanson, Gerber, Hutman, & Sigman, 2014), and Hanen's More Than Words program (Carter et al, 2011; Venker, McDuffie, Ellis Weismer, & Abbeduto, 2012). The results of the current study support the potential utility of behavioral ASD interventions to leverage nonsocial interests to improve social-communication functioning in children with ASD by gradually expanding the child's interests to include new objects, actions, and people.…”
Section: Discussionmentioning
confidence: 99%
“…Two programs obtained similarly favorable results with targeted social-communication skills and more global outcomes (Kasari, Gulsrud, Wong, Kwon, & Locke, 2010;Siller, Hutman, & Sigman, 2013). A secondary analysis of Siller's intervention indicated that this program was also associated with gains in some attachment-related behaviors (Siller, Swanson, Gerber, Hutman, & Sigman, 2014). Other RCTs have generally reported more favorable results for communication and social engagement outcomes than in global outcomes (e.g., ASD symptoms).…”
Section: Dsp Parent Trainingmentioning
confidence: 92%
“…The limited available evidence on parent training suggests that favorable response to treatment is moderated by baseline participant characteristics including object interest and more limited pretreatment communication skills (Siller, Swanson et al, 2014;Tonge et al, 2014). Other studies focused on predictors of outcome, such as the child's joint attention, involvement, enjoyment (Casenhiser et al, 2013), and age (Rogers et al, 2012); parent's intervention fidelity (Rogers et al, 2012) and quality of engagement (Kasari et al, 2010); and treatment ''dose'' (Rogers et al, 2012).…”
Section: Focused Interventionsmentioning
confidence: 99%